Effects of fluticasone propionate inhalation on levels of arachidonic acid metabolites in patients with chronic obstructive pulmonary disease - Gert T. Verhoeven; Ingrid M. Garrelds; Henk C. Hoogsteden; Freek J. Zijlstra (Hindawi Limited, 2001)
Background: In smoking COPD patients the bronchoalveolar lavage (BAL) fluid contains high numbers of inflammatory cells. These cells might produce arachidonic acid (AA) metabolites, which contribute to inflammation and an increased bronchomotor tone.